The Drawn Garden: Historical, Iconographical and Representative Analysis through Time of the “Villa Di Livia” in Rome - Martina Castaldi; Agostina Maria Giusto (Athens Journal of Architecture)
“Villa di Livia” at Prima Porta is an archaeological complex located in the suburban area of Rome. This villa was built in 39-38 B.D. at the behest of Livia Drusilla Claudia, the wife of Gaius Julius Caesar Augustus. The discovery of this complex took place in 1863 and brought to light several archaeological finds: one of particular aesthetic value are the frescoes with naturalistic motifs, where the attention to detail, the pictorial technique and the variety of flora and fauna make it one of the most famous examples of Roman garden motif painting. The aim of this research is to analyse the wall fresco decoration of the Villa. The investigation is historical, iconographic-representational and symbolic, in order to understand -on the one hand- the origin of these frescoes and the motivations that led to the choice of this particular type of representation and on the other hand- to study the decorative, perspective and colouring techniques. The work will try not to exclude the analysis of the fact that the architecture and the decorative apparatus are -currently- in different locations, which is certainly a benefit from the point of view of restoration and conservation, but may have an impact on the perception of the frescoes.